Evaluating Attributes, Traits, and Competencies of a School Leader: A Descriptive-Correlational Study - Leomarich Casinillo; Michael Suarez (Universitas Djuanda, 2022)
Evaluation of the different characteristics of a school leader in the Philippines is a bit limited in educational literature. Hence, this study focus on assessing the personal attributes, traits, and competencies of school leaders in the Hindang District, Leyte Division, Philippines to elucidate its nature and promote new policy in improving the educational system. This study employed a cross-sectional data gathering from a complete enumeration of teachers in the district. Mean, standard deviation, and coefficient of variation were computed in describing the survey data, and Spearman rho correlation was utilized in determining the association between variables. Results showed that school leaders are rated as